2021
DOI: 10.1021/acs.oprd.1c00258
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Static Mixer-Enabled Hydrogenation of a Key Fenebrutinib Intermediate: Real-Time Analysis for a Stable and Scalable Process

Abstract: Catalytic static mixer (CSM) technology is presented as an industrially viable solution for aromatic nitro group reduction in the synthesis of fenebrutinib. Factors affecting catalyst inhibition could be rapidly understood and mitigated by the use of real-time analytics (FT-IR and UHPLC). This facilitated the development of stable and optimal conditions in a system with four CSMs positioned inside a thermostated shell-and-tube reactor. Additional care was taken to ensure the control of three key impurities to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 50 publications
(32 reference statements)
0
20
0
Order By: Relevance
“…To solve the chemical compatibility issue, we turned our attention to Pd-CSMs, which are 3D-printed from chemically resistant stainless steel 316L . The nitro reduction was operated at the platform’s upper limit of 120 °C to suppress catalyst deactivation. , When we experimentally evaluated two Pd-CSMs in series with 2c starting material (Table , entries 3–4), the stainless steel scaffold was indeed chemically resistant to the DIPEA·HF byproduct, but deactivation was eventually observed after a few hours of operation. An attempt to regenerate the Pd catalyst in situ , did not restore the original catalyst activity (Figure C­(a)).…”
Section: Resultsmentioning
confidence: 99%
“…To solve the chemical compatibility issue, we turned our attention to Pd-CSMs, which are 3D-printed from chemically resistant stainless steel 316L . The nitro reduction was operated at the platform’s upper limit of 120 °C to suppress catalyst deactivation. , When we experimentally evaluated two Pd-CSMs in series with 2c starting material (Table , entries 3–4), the stainless steel scaffold was indeed chemically resistant to the DIPEA·HF byproduct, but deactivation was eventually observed after a few hours of operation. An attempt to regenerate the Pd catalyst in situ , did not restore the original catalyst activity (Figure C­(a)).…”
Section: Resultsmentioning
confidence: 99%
“…In the search for an industrially viable solution for catalytic aromatic nitro reduction of a drug intermediate, Kappe and co-workers deployed the catalytic static mixer technology and implemented a combined monitoring approach consisting of in-line FTIR spectroscopy and online UHPLC (Scheme ). While FTIR could differentiate reagents and products and quantify the concentrations and amounts of produced water, UHPLC gave a reaction progress overview. Thanks to 72 h FTIR data and >1100 online UHPLC samples, the catalyst-deactivation issue was understood and the reaction parameters were rapidly optimized.…”
Section: Discussionmentioning
confidence: 99%
“…Catalytic static mixers (CSMs) are specially designed 3D printed metal scaffolds which have been covered in a layer of catalyst through either electroplating or cold spray coating, for in-depth reviews of CSMs Tan et al and Lebl et al , Hydrogenation systems involving CSMs utilize the well-known tubular reactor (PFR) set up by simply being inserted into the reactor flow path for the reagent feed to flow through . Studies using CSMs have reported benefits such as good catalyst stability, little overall system pressure drop and minimal to no observed catalyst leaching into products . Other benefits of CSMs are that no postreaction workup is required to eliminate catalyst from the reaction mixture and because of their custom-made design CSMs are highly scalable .…”
Section: Continuous Flow Hydrogenation Technologiesmentioning
confidence: 99%
“…Other benefits of CSMs are that no postreaction workup is required to eliminate catalyst from the reaction mixture and because of their custom-made design CSMs are highly scalable . CSMs are actively being used within the pharmaceutical industry, with examples including Roche, with the University of Graz, who have been actively using this technology for nitro reductions of a fenebrutinib intermediate, and CSIRO the CSM manufacture as demonstrated by the synthesis of an intermediate of linezolid (Zyvox). …”
Section: Continuous Flow Hydrogenation Technologiesmentioning
confidence: 99%